Analisis Bersaing Menggunakan Strategi Pemasaran (4P) Pada Usaha Samko (Sembako) di Institut Shanti Bhuana - Isori Isori; Usman Usman (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The research carried out aims to find out what the problems are in running a basic food business by asking questions about the 4P (Product, Price, Place, Promotion) and finding out the relationship between selling basic food products to consumers. Promotion on consumer satisfaction in purchases such as pop noodles, snacks, and various sachet drinks, as well as vhocher, and drinks. This research was conducted on businesses that are run by business actors themselves. The background of the problem formulation is how the efforts made by Samko business actors overcome market competition in the dormitory environment at the Shanti Bhuana Institute. with the aim of explaining the specifics of what occurred and was resolved by incorporating various existing strategies in this research. The method used is a qualitative method. Subjective exploration is research used to study, discover, describe, and understand the characteristics or quality of social impacts that cannot be understood, estimated, or described through quantitative methodology. The implementation of the 4P marketing strategy implemented by basic food entrepreneurs has a real influence on the service that is always available every day so that the level of consumer satisfaction with the sale of Samko products, products, prices, locations, and promotional techniques carried out shows that the marketing strategy using the 4P.